IDENTIFICATION SPECIES OF STAPHYLOCOCCUS ISOLATED FROM POST-WEANING PIGLET TONSILS USING THE MORPHOLOGY, COAGULASE AND VOGES-PROSKAUER TEST - Aniendya Dyah Prasasti; I Wayan Suardana; I Wayan Sudira (Buletin Veteriner Udayana, 2025)
Tonsils are lymphoid tissue in the respiratory immune system that fights pathogens, but they can also harbor microbial colonization, such as Staphylococcus bacteria, which increases piglets' susceptibility to infection. Post weaning, piglets lose antibodies from colostrum, so their immune system is weakened and Gut Associated Lymphoid Tissue (GALT) is not yet functioning optimally in neutralizing microbes. Thus, this study was conducted to detect Staphylococcus sp. in the upper respiratory tract, namely tonsils in piglets. A total of 40 samples were obtained from a collection of presumptive Staphylococcus sp. isolates from Selat, Sangeh, and Taman Giri, Badung Regency, Bali. All samples were cultivated on blood agar media for 24 hours at 37°C. Colonies are followed by primary tests such as Gram staining and catalase test, and strengthened by biochemical tests such as coagulase test and Voges Proskauer test to clarify the identification of these bacteria, especially for identification as pathogenic bacteria. Of the 40 samples, the Staphylococcus species isolated were Staphylococcus epidermidis (27.5%), Staphylococcus hyicus (27.5%), Staphylococcus aureus (25%), and Staphylococcus saprophyticus (20%). This study concluded that the tonsils were mostly occupied by commensal and potentially pathogenic bacteria (S. epidermidis and S. hyicus), which have the potential to trigger skin and systemic infections. Therefore, maintaining the cleanliness of the barn, providing balanced nutrition, and biosecurity of the barn need to be done as an effort to control and prevent Staphylococcus sp. bacterial infections in post-weaning piglets.